What are the barriers and facilitators to community handwashing with water and soap? A systematic review - Obidimma Ezezika; Jennifer Heng; Kishif Fatima; Ayman Mohamed; Kathryn Barrett (Public Library of Science (PLoS), 2023)
Handwashing with water and soap (HWWS) is an effective method of cleaning and disinfecting the surface of the hands. HWWS is effective in infection control and prevention transmission, such as in Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). However, rates of handwashing compliance vary globally. This systematic review aimed to identify the barriers and facilitators to community HWWS globally. We conducted a comprehensive search strategy in OVID Medline, OVID Embase, Web of Science Core Collection, and Scopus using keywords and subject headings related to handwashing. Studies were excluded if they reported hand hygiene among healthcare or food service workers, considered the use of alcohol rubs, or involved an intervention in a healthcare or food preparation setting. The quality of eligible studies was assessed using the Mixed Methods Appraisal Tool, and data were extracted from the articles and analyzed using the Theoretical Domains Framework and inductive thematic analysis. The search strategy yielded a total of 11,696 studies, and 46 studies met the eligibility criteria. Study dates ranged from 2003 to 2020 and included 26 countries; the most frequently represented were Bangladesh, India, and Kenya. A total of 21 barriers and 23 facilitators to HWWS were identified and organized into the Theoretical Domains Framework. The most frequently cited domains were environmental context and resources, goals, and knowledge. Nine themes emerged from these barriers and facilitators: resource availability, cost and affordability, handwash station design and infrastructure, accessibility, gender roles, champions, health promotion, time management, and knowledge, beliefs, and behaviors. This review uncovered multiple barriers and facilitators around a determinant framework to observe and create an in-depth, multidimensional image of a community-based hand hygiene situation. New comprehensive interventions and implementation strategies can be developed using the findings to target the contextual barriers and facilitators to improve and increase HWWS rates. Stakeholders (i.e., practitioners, researchers, policymakers) can use the findings to revise, design, or evaluate new or existing projects, interventions, and policies to improve HWWS. Registration: A protocol for this systematic review was developed and uploaded onto the PROSPERO-International prospective register of systematic reviews database (Registration number: CRD42020221210).